ANALISIS PERENCANAAN STRATEGI PEMBANGUNAN KELURAHAN KARANGREJO - Azka Dwi Fachrurazi; Tiara Cipta Wijayanti; Siti Aisyah; Sevira Destyfani; Nurgapita Puspaningrum; Shindy Dewi Lastari (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This research analyzes related development strategy planning in Karangrejo Village, Jember Regency. By using qualitative methods and designing Karangrejo sub-district strategies. The results show that development planning in the Karangrejo sub-district has gone well, because there is cooperation between the village government and the Karangrejo sub-district community. Development planning is also almost running perfectly. It’s just that there are several obstacles, such as differences of opinion from some people regarding planning proposals aimed at government programs that will be implemented, and another obstacle is related to funding from the government which means the planning is not fully realized.